The role of fibrinogen combined with platelet-rich plasma in enhancing microfracture for cartilage damage: a retrospective study of 113 patients with knee osteoarthritis - Qiongmei Zhang; Haolin Zhou; Daoxiong Li; Yuan Zhong; Ye-Feng Zhao; Jianfeng Yan; Hongxiao Zhao (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Objective Knee osteoarthritis is the most common osteoarthritis and imposes a significant burden on patients’ lives. Several treatment methods can promote cartilage repair to varying extents, but there are limited studies on the combined application of different treatments. The purpose of this study is to evaluate the clinical efficacy of microfracture combined with fibrinogen and platelet-rich plasma (PRP) under arthroscopic in treating knee osteoarthritis, so as to provide a basis for clinical treatment decisions. Method A total of 113 patients with knee osteoarthritis who received orthopedic treatment from January 2021 to June 2022 were selected. They were divided into two groups according to whether they received fibrinogen and PRP treatment in addition to microfracture treatment. The two groups were analyzed to compare the differences in knee joint function and quality of life at different points. Results The study compared changes in knee joint function scores and quality of life between the two groups after treatment and found that the quality of life of patients in the combined treatment group was significantly better than that of patients who received microfracture only (at 12-month follow-up, EuroQol-VAS scores were 64.32 ± 5.63 for the microfracture group (MFx) and 75.65 ± 8.57 for the fibrinogen combined with platelet-rich plasma-assisted microfracture group (FPRPA MFx); P = 0.015; at 24-month follow-up, EuroQol-VAS scores were 66.47 ± 5.18 for the MFx group and 79.40 ± 7.43 for the FPRPA MFx group, P = 0.022). There was also a strong correlation between patients’ quality of life and knee joint function score index (IKDC score correlation coefficient r=-0.375, Lysholm score correlation coefficient r = 0.497, MOCART score correlation coefficient r = 0.579, VAS score correlation coefficient r = 0.242, T2 value correlation coefficient r=-0.293, P < 0.001). Age-stratified analysis of the patients in the microfracture combined with fibrinogen platelet-rich plasma treatment group showed that the effect of the combined treatment was more pronounced in elderly patients. Conclusions The results of the study showed that compared with microfracture alone, microfracture combined with fibrinogen platelet-rich plasma therapy can further improve patients’ knee joint-related function and their quality of life after treatment. The improvement was more obvious in elderly patients.